Green low-carbon glass insulator and preparation method thereof
Patent Information
- Application Number
- CN202611248621.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]现有技术中,将氧化钇与碳化硅晶须、改性壳聚糖协同复配,并以多巴胺改性钠长石负载石墨烯作为调节剂,应用于玻璃绝缘子的研究未见报道
本发明以玻璃基料为主体,通过改性氧化钇剂与石墨烯调节剂的协同复配,实现了玻璃绝缘子力学性能、介电性能和耐候性能的同步提升。改性氧化钇剂中碳化硅晶须的晶须增强效应、改性壳聚糖的“分子桥”偶联作用和纳米二氧化硅的致密化效应协同作用于氧化钇,使其在玻璃基体中的分散性和改性效率显著增强;石墨烯调节剂以多巴胺改性钠长石为载体负载石墨烯,有效抑制石墨烯团聚。二者协同构建了“晶须-纳米-层状”多尺度增强体系。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of insulator technology, specifically to a green, low-carbon glass insulator and its preparation method. Background Technology
[0002] Glass insulators, as key components of power transmission and distribution systems, possess advantages such as good light transmittance, smooth surface that is not prone to dirt accumulation, and long service life, making them widely used in high-voltage transmission lines. With the power industry's continuously increasing demands for insulator performance, improving the mechanical strength, thermal shock resistance, and dielectric properties of glass insulators has become a key focus of technological research.
[0003] Introducing functional fillers into glass matrices is an effective way to improve performance. Yttrium oxide (Y₂O₃), as a rare earth oxide, can participate in the modification of glass network structures, reducing melt viscosity, improving density and dielectric properties; however, its uneven dispersion in the glass matrix limits the modification effect. Silicon carbide whiskers (SiCw) possess high strength, high modulus, high temperature resistance, and good chemical stability, making them ideal reinforcing components for ceramic matrix composites; however, their strong surface inertness and poor compatibility with the glass matrix are problematic. Chitosan, as a natural polymer rich in hydroxyl and amino groups, can be chemically modified and used as a coupling agent to improve the interfacial bonding between inorganic fillers and the matrix; however, its application in glass insulators has been rarely reported.
[0004] Graphene possesses excellent mechanical, electrical, and thermal conductivity, and as a reinforcing phase, it can significantly improve the overall performance of composite materials. However, the strong van der Waals forces between graphene sheets make it prone to agglomeration in inorganic matrices, hindering uniform dispersion. Albite, as a framework silicate mineral, exhibits good chemical stability and compatibility with glass systems, making it a suitable dispersion carrier for graphene. Dopamine hydrochloride can self-polymerize under weakly alkaline conditions to form a polydopamine layer, imparting surface adhesion and reactivity to materials; however, research on its application in modifying albite to support graphene remains lacking.
[0005] In the existing technology, there are no reports on the application of yttrium oxide synergistically compounded with silicon carbide whiskers and modified chitosan, and with dopamine-modified sodium feldspar-supported graphene as a modifier, in glass insulators. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a green and low-carbon glass insulator and its preparation method, so as to solve the problems mentioned in the background art.
[0007] The present invention solves the technical problem by adopting the following technical solution: This invention provides a green, low-carbon glass insulator, comprising the following raw materials in parts by weight: 80-92 parts glass matrix, 5-12 parts modified yttrium oxide agent, 3-8 parts graphene modifier, and 2-5 parts flux.
[0008] Preferably, the glass base is sodium-calcium silicate glass powder or borosilicate glass powder; the flux is borax and / or sodium carbonate.
[0009] Preferably, the modified yttrium oxide is prepared by: S01: By weight, add 6-15 parts of silicon carbide whiskers, 4-10 parts of modified chitosan and 5-12 parts of silica to 50-70 parts of deionized water, and ultrasonically disperse for 30-60 minutes to obtain a mixture; SO2: Add 8-18 parts of yttrium oxide to the mixture and stir the mixture at 300-500 r / min for 2-5 h under water bath conditions at 50-80℃; S03: After the reaction is completed, the modified yttrium oxide is obtained by filtration, washing, drying at 80-110℃ and grinding.
[0010] The modified yttrium oxide agent uses yttrium oxide as the main agent, through the synergistic modification of silicon carbide whiskers, modified chitosan, and nano-silica. The high strength and high modulus of silicon carbide whiskers can form a whisker reinforcement network in the glass matrix, improving the flexural strength and impact resistance of the product. After grafting with a silane coupling agent, modified chitosan introduces epoxy or silanol active sites onto its molecular chain, which can simultaneously form chemical bonds with the hydroxyl groups on the surface of the inorganic filler and the glass matrix, acting as a "molecular bridge" to improve the compatibility and bonding force of the multiphase interface. Simultaneously, its organic components can pyrolyze during low-temperature treatment to form carbon templates, further optimizing the interface structure. Nano-silica can fill micropores and increase density. After multi-component synergistic coating modification, the dispersibility and reactivity of yttrium oxide in the glass melt are significantly improved.
[0011] Preferably, the modified chitosan is prepared by dissolving chitosan in an aqueous solution of acetic acid with a mass fraction of 2-5%, adding γ-glycidyl etheroxypropyltrimethoxysilane (KH560) at a mass fraction of 5-15% of the chitosan, stirring and reacting at 50-70°C for 2-4 hours, and obtaining modified chitosan by precipitation, washing, and drying.
[0012] Preferably, the silicon carbide whiskers have a diameter of 0.5–3 μm and an aspect ratio of (10–50):1; the yttrium oxide has a particle size of 10–100 nm; and the silicon dioxide is nano-silicon dioxide with a particle size of 20–80 nm.
[0013] Preferably, the graphene modifier is prepared by: S11: By weight, 5-12 parts of sodium feldspar powder are added to 30-50 parts of 0.5-2% dopamine hydrochloride solution, and the mixture is stirred and reacted at 25-40℃ for 4-8 hours. After filtration, washing and drying, dopamine-modified sodium feldspar is obtained. S12: Mix 3-8 parts of graphene with dopamine-modified albite, add to 40-60 parts of deionized water, ultrasonically disperse for 20-40 min, and stir at 400-600 r / min at 60-80℃ for 1-3 h. S13: After the reaction is completed, the graphene regulator is obtained by filtration, washing, drying at 80-105℃ and grinding.
[0014] The graphene modifier uses albite as a carrier. After modification with dopamine hydrochloride, a polydopamine coating layer forms on the surface of the albite, endowing it with abundant catechol and amino active sites. These groups can form a strong bond with graphene through π-π stacking and hydrogen bonding, effectively inhibiting the aggregation of graphene sheets. The framework silicate structure of albite and its good compatibility with glass systems make it an efficient dispersion carrier for graphene in glass matrices. The introduction of graphene can improve the mechanical properties and thermal conductivity uniformity of glass insulators. However, its electrical conductivity must be strictly controlled in the amount added to the insulating material to avoid degradation of insulation performance.
[0015] Preferably, the albite powder has a particle size of 1–20 μm; the graphene is graphene oxide or reduced graphene oxide with a sheet diameter of 1–10 μm.
[0016] This invention also provides a method for preparing a green, low-carbon glass insulator, comprising the following steps: Step 1, Mixing: Add the glass matrix, modified yttrium oxide agent, graphene modifier, and flux to a ball mill according to the specified ratio and mix evenly. After drying and sieving, a mixed powder is obtained. Step 2, Melting: The mixed powder is put into the melting furnace and melted at 1420-1520℃ for 2.5-5 hours. After clarification and homogenization, the glass melt is obtained. Step 3: Molten glass is poured into an insulator mold to form a green insulator blank. Step 4: Annealing: Anneal the insulator blank at 520-650℃ for 1-3 hours, and then cool it to room temperature in the furnace to obtain green low-carbon glass insulator.
[0017] Preferably, the ball milling mixing time in step one is 2 to 5 hours; the melting temperature in step two is preferably 1450 to 1500°C.
[0018] Beneficial effects This invention uses glass as the main material and achieves simultaneous improvement in the mechanical, dielectric, and weather resistance properties of glass insulators through the synergistic compounding of modified yttrium oxide and graphene modifier. The whisker reinforcement effect of silicon carbide whiskers, the "molecular bridge" coupling effect of modified chitosan, and the densification effect of nano-silica in the modified yttrium oxide synergistically enhance the dispersion and modification efficiency of yttrium in the glass matrix. The graphene modifier uses dopamine-modified albite as a carrier to support graphene, effectively inhibiting graphene agglomeration. Together, they construct a multi-scale reinforcement system of "whisker-nano-layered" structures.
[0019] In modified yttrium oxide, the high temperature resistance and high strength of silicon carbide whiskers improve the flexural and impact resistance of the products; modified chitosan grafted with KH560 introduces epoxy active groups, which can form chemical bonds between inorganic fillers and glass matrix, improve interfacial compatibility and optimize the microstructure of the interfacial transition zone; the filling effect of nano-silica increases density. The rare earth network modification effect of yttrium oxide further optimizes the glass structure and improves dielectric properties.
[0020] In the graphene modifier, the polydopamine layer formed by the self-polymerization of dopamine hydrochloride endows the surface of albite with adhesion activity and reaction sites, efficiently loading graphene through π-π stacking and hydrogen bonding, preventing its agglomeration. Albite, as a dispersion carrier, utilizes its good chemical compatibility with the glass system to uniformly introduce graphene into the glass matrix, achieving the micro-nano reinforcement effect of graphene. This invention, through the synergistic design of various functional components and an optimized low-temperature melting process (1420–1520℃), reduces production energy consumption and carbon emissions, realizing the green and low-carbon manufacturing of glass insulators, which aligns with the national "dual-carbon" strategy and the direction of green manufacturing development. Detailed Implementation
[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Example 1 A green, low-carbon glass insulator comprises the following raw materials in parts by weight: 84 parts of sodium-calcium silicate glass powder, 8 parts of modified yttrium oxide agent, 5 parts of graphene modifier, and 3 parts of borax.
[0023] Preparation of modified yttrium oxide: 10 parts of silicon carbide whiskers (diameter 1.5 μm, aspect ratio 30:1), 7 parts of modified chitosan, and 8 parts of nano-silica (particle size 50 nm) were added to 60 parts of deionized water and ultrasonically dispersed for 45 min. Then, 13 parts of yttrium oxide (particle size 50 nm) were added, and the mixture was stirred at 400 r / min for 3.5 h in a 65 °C water bath. After filtration and washing, the mixture was dried and ground at 100 °C. Modified chitosan was prepared by dissolving chitosan in a 3% acetic acid aqueous solution, adding 10% KH560, and reacting at 60 °C for 3 h.
[0024] Preparation of graphene modifier: 8 parts of sodium feldspar powder were added to 40 parts of 1% dopamine hydrochloride solution and stirred at 30℃ for 6 hours. After washing and drying, it was mixed with 5 parts of graphene oxide (sheet diameter 5 μm), 50 parts of deionized water were added, and the mixture was sonicated for 30 minutes. It was stirred at 70℃ at 500 r / min for 2 hours, filtered, washed, dried and ground at 95℃.
[0025] Preparation method: The raw materials are ball-milled and mixed for 4 hours, melted at 1480℃ for 3.5 hours, cast into shape, annealed at 580℃ for 2 hours, and cooled in the furnace.
[0026] Example 2 Raw materials: 80 parts borosilicate glass powder, 5 parts modified yttrium oxide agent, 3 parts graphene modifier, and 2 parts sodium carbonate. The modified yttrium oxide agent was prepared using 6 parts silicon carbide whiskers, 4 parts modified chitosan, 5 parts silicon dioxide, and 8 parts yttrium oxide; the graphene modifier was prepared using 5 parts albite and 3 parts graphene. The preparation method is the same as in Example 1.
[0027] Example 3 Raw materials: 92 parts of sodium-calcium silicate glass powder, 12 parts of modified yttrium oxide, 8 parts of graphene modifier, and 5 parts of borax. The modified yttrium oxide was prepared using 15 parts of silicon carbide whiskers, 10 parts of modified chitosan, 12 parts of silicon dioxide, and 18 parts of yttrium oxide; the graphene modifier was prepared using 12 parts of albite and 8 parts of graphene. The preparation method is the same as in Example 1.
[0028] Scale settings Comparative Example 1: No modified yttrium oxide agent was added, only graphene modifier was added.
[0029] Comparative Example 2: No graphene modifier was added, only modified yttrium oxide was added.
[0030] Comparative Example 3: No silicon carbide whiskers were added during the preparation of the modified yttrium oxide agent.
[0031] Comparative Example 4: No modified chitosan was added during the preparation of the modified yttrium oxide agent (it was replaced with an equal amount of unmodified chitosan).
[0032] Comparative Example 5: Sodium feldspar was not modified with dopamine hydrochloride in the preparation of graphene modifier.
[0033] Comparative Example 6: No albite was added during the preparation of the graphene modifier (graphene was used directly).
[0034] Performance testing
[0035] The test results show that Examples 1-3 exhibit excellent performance in flexural strength (92.8-108.6 MPa), volume resistivity (2.58-3.21 × 10¹³ Ω·cm), thermal shock resistance (270-300℃), and UV aging strength retention (91.2-95.1%). Comparative Examples 1-2 confirm that both the modified yttrium oxide agent and the graphene modifier are indispensable; adding either significantly reduces performance. Comparative Examples 3-4 demonstrate that silicon carbide whiskers and modified chitosan are the core functional components of the modified yttrium oxide agent. Comparative Examples 5-6 confirm that dopamine hydrochloride modification and albite carrier play a crucial role in the effectiveness of the graphene modifier. This invention achieves a significant improvement in the overall performance of glass insulators through multi-component synergistic compounding and employs a relatively low-temperature melting process, meeting the requirements of green and low-carbon manufacturing.
[0036] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0037] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A green, low-carbon glass insulator, characterized in that, It includes the following raw materials in parts by weight: 80-92 parts glass matrix, 5-12 parts modified yttrium oxide agent, 3-8 parts graphene modifier, and 2-5 parts flux.
2. The green low-carbon glass insulator according to claim 1, characterized in that, The glass base material is sodium-calcium silicate glass powder or borosilicate glass powder; the flux is borax and / or sodium carbonate.
3. The green low-carbon glass insulator according to claim 1, characterized in that, The preparation method of the modified yttrium oxide is as follows: S01: By weight, add 6-15 parts of silicon carbide whiskers, 4-10 parts of modified chitosan and 5-12 parts of silica to 50-70 parts of deionized water, and ultrasonically disperse for 30-60 minutes to obtain a mixture; SO2: Add 8-18 parts of yttrium oxide to the mixture and stir the mixture at 300-500 r / min for 2-5 h under water bath conditions at 50-80℃. S03: After the reaction is completed, the modified yttrium oxide is obtained by filtration, washing, drying at 80-110℃ and grinding.
4. A green, low-carbon glass insulator according to claim 3, characterized in that, The modified chitosan is prepared by dissolving chitosan in an aqueous solution of acetic acid with a mass fraction of 2-5%, adding γ-glycidyl etheroxypropyltrimethoxysilane at a mass fraction of 5-15% of the chitosan, stirring and reacting at 50-70°C for 2-4 hours, and then precipitating, washing, and drying to obtain the modified chitosan.
5. A green, low-carbon glass insulator according to claim 3, characterized in that, The silicon carbide whiskers have a diameter of 0.5–3 μm and an aspect ratio of (10–50):1; the yttrium oxide has a particle size of 10–100 nm; and the silicon dioxide is nano-silicon dioxide with a particle size of 20–80 nm.
6. A green, low-carbon glass insulator according to claim 1, characterized in that, The preparation method of the graphene modifier is as follows: S11: By weight, 5-12 parts of sodium feldspar powder are added to 30-50 parts of 0.5-2% dopamine hydrochloride solution, and the mixture is stirred and reacted at 25-40℃ for 4-8 hours. After filtration, washing and drying, dopamine-modified sodium feldspar is obtained. S12: Mix 3-8 parts of graphene with dopamine-modified albite, add to 40-60 parts of deionized water, ultrasonically disperse for 20-40 min, and stir at 400-600 r / min at 60-80℃ for 1-3 h. S13: After the reaction is completed, the graphene regulator is obtained by filtration, washing, drying at 80-105℃ and grinding.
7. A green, low-carbon glass insulator according to claim 6, characterized in that, The albite powder has a particle size of 1–20 μm; the graphene is graphene oxide or reduced graphene oxide with a sheet size of 1–10 μm.
8. A method for preparing a green low-carbon glass insulator as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1, Mixing: Add the glass matrix, modified yttrium oxide agent, graphene modifier, and flux to a ball mill according to the specified ratio and mix evenly. After drying and sieving, a mixed powder is obtained. Step 2, Melting: The mixed powder is put into the melting furnace and melted at 1420-1520℃ for 2.5-5 hours. After clarification and homogenization, the glass melt is obtained. Step 3: Molten glass is poured into an insulator mold to form a green insulator blank. Step 4: Annealing: Anneal the insulator blank at 520-650℃ for 1-3 hours, and then cool it to room temperature in the furnace to obtain green low-carbon glass insulator.
9. The preparation method according to claim 8, characterized in that, In step one, the ball milling mixing time is 2 to 5 hours; in step two, the preferred melting temperature is 1450 to 1500℃.